Pragmatic Language Skills: A Comparison of Children With Cochlear Implants and Children Without Hearing Loss - Socher, Michaela; Lyxell, Björn; Ellis, Rachel; Gärskog, Malin; Hedström, Ingrid; Wass, Malin (Frontiers in Psychology, 2019)
Pragmatic language ability refers to the ability to use language in a social context. It has been found to be correlated with success in general education for deaf and hard of hearing children. It is therefore of great importance to study why deaf and hard of hearing children often perform more poorly than their hearing peers on tests measuring pragmatic language ability. In the current study the Pragmatics Profile questionnaire from the CELF-IV battery was used to measure pragmatic language ability in children using cochlear implants (N = 14) and children without a hearing loss (N = 34). No significant difference was found between the children with cochlear implants (CI) and the children without hearing loss (HL) for the sum score of the pragmatics language measure. However, 35.71% of the children with CI performed below age norm, while only 5.89% of the children without HL performed below age norm. In addition, when dividing the sum score into three sub-measures: Rituals and Conversational skills (RCS), Asking for, Giving, and Responding to Information (AGRI), and Nonverbal Communication skills (NCS), significant differences between the groups were found for the NCS measure and a tendency for a difference was found for the RCS measure. In addition, all three sub-measures (NCS, AGRI, RCS) were correlated to verbal fluency in the children with CI, but not the children without HL.